Pertumbuhan Ipomoea reptans Poir. dengan Aplikasi The Kompos Serat Bromelain Terinduksi Trichoderma sp. dan Aspergillus sp. - Masnoni Firda Safira; Bambang Irawan; Christina Nugroho Ekowati; Rochmah Agustrina (Jurnal Ilmu Pertanian Indonesia, 2024)
Bromelain fiber is the product of extracting the enzyme bromelain from pineapple hulls or peels. Bromelain fiber contains lignocellulose, which, when fully decomposed, is very beneficial for the environment, but it is quite challenging to degrade naturally. Hence, it requires a decomposer agent. The decomposer agents used in this study were cellulolytic fungi Aspergillus sp. (Bioggp 3) and ligninolytic Trichoderma sp. (Bioggp 2). This study aims to determine the effect of compost tea (CT) bromelain fiber induced by these fungi and obtain the best dose of the CT on the growth of land kale (Ipomoea reptans Poir.). This research was conducted in April–July 2022 at the Microbiology Laboratory of FMIPA Unila. This study used a completely randomized design (CRD) with 7 treatments and 4 replications, namely P0 (control), P1 (ACT 25%), P2 (NACT 25%), P3 (ACT 50%), P4 (NACT 50%), P5 (ACT 75%), P5 (NACT 75%). The parameters measured were plant height and number of leaves. The data were analyzed using ANOVA α = 5% followed by the Least Significant Difference (LSD) test with a 5% confidence interval. This study showed that the results with the highest height value and number of leaves were found in P3 (ACT 50%) while the lowest was in P0 (water control). It can be concluded that the ACT and NACT significantly affect the height and number of leaves, and the best dose was found in ACT 50% starting from day 10, 15 , 20, and 25 after planting. Keywords: Aspergillus sp., bromelain fiber, compost tea, Ipomoea reptans Poir, Trichoderma sp.